A NOVEL THROMBIN-LIKE GENE OBTAINED FROM CHINESE GLOYDIUS SHEDAOENSIS SHEDAOENSIS - Chunmei Guo; Shuqing Liu; Tihua Zheng; Ming-Zhong Sun (Journal of Animal and Plant Sciences, 2013)
The snake of Gloydius shedaoensis shedaoensis (GSS) is the particular and sole snake species from Shedao island in Dalian, China. A novel gene named as GSSG-TLE was cloned from GSSG by PCR using GSSG-cDNA library plasmid as template. The GSSG-TLE cDNA was sequenced and encompasses an open reading frame of 786 bp in length and encoding a protein of 262 amino acid residues. The GSSG-TLE gene has a base composition of 14 Ala, 12 Cys, 14 Asp, 13 Glu, 10 Phe, 19 Gly, 7 His, 20 Ile, 15 Lys, 25 Leu, 4 Met, 12 Asn, 19 Pro, 7 Gln, 12 Arg, 20 Ser, 14 Thr, 13 Val, 5 Trp and 7 Tyr. GSSG-TLE includes a signal peptide of 18 amino acids, a proposed propeptide of 6 amino acids and a matured peptide of 238 amino acids. It also contains 12 Cys which form 6 disulfide bridges and has three conserved catalytically active sites of His67, Asp112 and Ser202. Sequence comparison revealed that GSSG-TLE amino acids sequence shared highly identity with other snake venom thrombin-like enzymes.
Keywords: Gloydius shedaoensis shedaoensis; Snake; Thrombin-like enzyme